Impact and Association of Anaemia Severity and Its Treatment With Quality of Life of Breast Cancer Patients in Malaysia - Mohammed, Ali Haider; Muthanna, Fares Mohammed Saeed; Hassan, Bassam Abdul Rasool; Karuppannan, Mahmathi; Wayyes, Abdulrasool M. (Iraqi Journal of Pharmaceutical Sciences, 2022)
Anaemia is a crucial issue among cancer patients and need to be treated properly. High incidence of anaemia in patients with cancer have been associated with several physiological manifestations, leading to decreased quality of life (QOL).The current study aimed to assess the severity of anaemia, evaluate the current treatment guideline of anaemia, and to determine the association between the level of anaemia and its treatment on quality of life of breast cancer patients in Malaysia. This prospective study conducted among breast cancer patients in multicancer centers in Malaysia including three follow ups after receiving their chemotherapy. Clinical data were collected from their medical records and at each follow up, they asked to fill up a functional assessment chronic therapy (FACT-An) questionnaire. Descriptive and inferential statistical analysis were done using SPSS. The mean age of participants was 52 ± 11 years old, and out of 120 participants, 32% received anti-anaemic treatments including 87% of them were prescribed with iron supplementation and only 13% received combination of blood transfusion and iron therapy. Surprisingly, none of the participants received erythropoietin stimulating agents (ESAs). Statistical tests also indicated a significant association between anti-anaemic treatments with haemoglobin level and QOL scores. However, this association was insufficient to significantly improve QOL or palliate anaemia severity among participants.This study showed a great evidence that, the current practice of anaemia treatment (iron therapy) among breast cancer patients in Malaysia’s healthcare setting, was not sufficient to palliate anaemia severity or to improve patients’ QOL. There is still a lot of gaps to improve in the management of anaemia among breast cancer patients to show a significant improvement in haemoglobin level. Therefore, respective organisations and oncologists are required to raise awareness about the optimal treatment of anaemia among breast cancer patients, as a result, improve their general wellbeing